Sex Differences in Clinical Characteristics and Brain MRI Change in Patients With Wilson’s Disease in a Chinese Population - Li, Xiaohu; Feng, Zhiqiang; Tang, Wei; Yu, Xuen; Qian, Yinfeng; Liu, Bin; Li, Xiaoshu; Yang, Renmin; Yu, Yongqiang (Frontiers in Physiology, 2018)
Background: Wilson’s disease (WD) is an inborn copper metabolism disease. Sex differences in clinical features of WD patients have been reported; however, the effect of sex on brain MRI is still unclear, especially for Chinese WD patients. Therefore, we aimed to examine sex differences in clinical correlates and brain MRI changes in WD patients in a Chinese Han population. Methods: 535 WD patients were enrolled and underwent MRI scanning. These patients were subdivided by the clinical symptoms, Kayser–Fleischer (K–F) rings, laboratory tests and sex. The mean age of onset and diagnosis, disease latency, localization of brain MRI lesions, and the level of copper metabolism were compared between male and female patients. Results: The neuropsychiatric form (452 and 84.5%) was the most common subtype. Compared to female patients, male patients had a higher percentage in three clinical forms: neuropsychiatric form (263 and 58.2%), hepatic form (41 and 59.4%), and presymptomatic form (10 and 71.4%). In the neuropsychiatric form, male patients had the earlier age of onset and definitive diagnosis, and shorter time of disease latency than female patients. Putamen was the most common site for lesions in brain MRI of three groups. In the hepatic form, more male patients showed the ventricular widening than female patients (14/41 vs. 3/28; p < 0.05). The level of serum ceruloplasmin and copper of WD patients with neuropsychiatric form was higher than that of male patients with hepatic or presymptomatic form. In women, however, patients of presymptomatic form have the highest level of the ceruloplasmin, and the level of serum copper in hepatic patients was highest. Conclusion: Our findings suggest sex differences in the percentage of three clinical forms. Meanwhile, the mean age of onset and diagnosis of female was higher than male, also happened in the disease latency. Only in the hepatic form, there was a sex difference in the ventricular widening.